An unexpected diversity of Cyphophthalmi (Arachnida: Opiliones) in Upper Cretaceous Burmese amber - Bartel, Christian; Dunlop, Jason A.; Giribet, Gonzalo (Zootaxa, 2023)
Ten new Cyphophthalmi specimens (Arachnida: Opiliones) from the Upper Cretaceous (Lower Cenomanian) Burmese amber of northern Myanmar are described. Seven of these are placed in Stylocellidae, the predominant extant family found today in Southeast Asia. Sirocellus iunctus gen. et sp. nov. represents the first fossil with a combination of sironid and stylocellid characters, suggesting a still ongoing transition in some lineages during the Upper Cretaceous. Mesopsalis oblongus gen. et sp. nov. represents a second fossil with elongated ozophores, a character not known from modern species. Leptopsalis breyeri sp. nov. is the first Cretaceous cyphophthalmid assignable to an extant genus. The species Foveacorpus cretaceus gen. et sp. nov. and F. parvus gen. et sp. nov., which cannot be placed in an extant family, show morphological novelties for Cyphophthalmi such as numerous pits covering the whole body. The possible function of these pits is discussed. Three more adult males with unique adenostyles and two juveniles are not formally named but further indicate an already highly diverse cyphophthalmid fauna during the Cretaceous. The total number of named Burmese amber Cyphophthalmi species is raised from one to six, and the total fossil record for this suborder now stands at eight.